Working Memory Capacity, TL Grammar Attainment and Length of Study as Predictors of Explicit and Implicit (Automatized) Knowledge of English Passive Voice - Biedroń Adriana; Pasikowski Sławomir; Pawlak Mirosław (Psychology of Language and Communication)
This study investigated the relationship between phonological short-term memory (PSTM), working memory capacity (WMC), and receptive and productive dimensions of explicit and implicit (automatized) knowledge of English passive voice, also taking into account the effect of grammar attainment and self-reported length of study. Participants were 152 Polish university students majoring in English. Two measures of PSTM and WMC were applied. Receptive and productive explicit knowledge were measured by means of an untimed grammaticality judgment test and a test requiring the provision of correct verb forms, respectively. Receptive implicit (automatized) knowledge was assessed with a timed grammaticality judgment test while its productive dimension was assessed through a focused communication task. Canonical correlation for the entire model was rather high, which means that the original variables were strongly related to each other. However, finer-grained analyses showed that it was primarily overall grammar attainment, and, to a lesser extent, WMC that determined the levels of explicit and implicit (automatized) grammar knowledge.